Estrategias de la actividad física para prevención de la obesidad en niños entre 6 y 12 años en la Ciudadela Av. Universitaria - Alvarado López, Otto Alessandro (2022)
Physical activity is considered as a healthy alternative to guarantee good health, so its application is recommended in all stages of life and following the guidance of professionals to obtain the expected results, in this way, in the present research project. The strategies of physical activity for the prevention of obesity in children between 6 and 12 years old in the Av. Universitaria citadel are analyzed. At present, there are many activities that are related to technology and that distance children more and more from physical activity, sedentary lifestyle resulting from the distance from physical activity does not allow them to leave the comfort zone, which makes their motivation more difficult and necessary, which the present study makes clear and which demonstrates this need. The methodology used in the present research project is qualitative and quantitative, it is based on the types of descriptive research to describe the findings in detail and exploratory, at the time of deepening the study with the documentary modalities for the collection of information. Theoretical and field foundation to apply the information gathering techniques in the place of the facts, the study population is the inhabitants of the citadel Av. Universitaria to whom a questionnaire of open and closed questions was applied and that showed that the boys and girls who do not perform physical activity present obesity problems and health complications, generating as an alternative the design of a physical activity strategy plan to prevent and reduce obesity in children between 6 and 12 years in the citadel av. University.